Reducing CO2 emissions from the ferro-alloy and silicon production - M Tangstad; G M. Tranell (The Australasian Institute of Mining and Metallurgy, 2024)
The CO2 footprints in the production of Mn-ferroalloys and silicon/ferrosilicon are correlated with the fossil carbon consumption. The CO2 emissions may be reduced in the Mn-ferroalloy process by increasing the degree of prereduction and reduction of carbonate materials, while the silicon/ferrosilicon process is optimised based on silicon yield. By changing the fossil reductant into biogenic reductants, the global warming potential will be decreased even more. Even if the reductants are biogenic reductants, there will still be a global warming potential (GWP) in eg the electrode consumption and the CH4 emissions in the charcoal production. To reduce the use of fossil reductants there are also more disruptive technologies like the use of H2 that at least for the silicon production is on a very low technology readiness level (TRL). Using metallothermic processes will reduce the use of carbon but requires carbon neutral metal reductants. Electrowinning can have low CO2 emissions, and the electrowinning of pure Mn is a technology of high TRL. Salt and oxide electrolysis is under investigation for both Mn and Si production however the research is still on a low TRL. The use of CCS/CCU (carbon capture storage/utilisation) is a part of obtaining carbon neutral processes. Last, the energy mix used for these energy demanding processes is discussed.